Pengaruh Kurs Rupiah, BI7DRR dan Indeks Harga Saham Gabungan terhadap Harga Saham PT Bank bjb tbk yang Terdaftar di Bursa Efek Indonesia - Agus Saeful Saeful; Ida Rapida; Nur'aeni Nur'aeni (Ma'soem University, 2021)
Based on the data that has been obtained, this research is motivated by fluctuations in stock prices which are influenced by external factors, namely the rupiah exchange rate, BI7DRR and JCI. This study aims to determine the effect of the rupiah exchange rate on the stock price of PT Bank BJB TBK, the effect of BI7DRR on the stock price of PT Bank BJB, the effect of the JCI on the stock price of PT Bank BJB TBK, knowing how the effect of the rupiah exchange rate, BI7DRR, and JCI on the stock price of PT Bank BJB TBK listed on the 2016-2020 Stock Exchange. The object of research is the rupiah exchange rate, BI7DRR, JCI and the share price of PT Bank BJB Tbk which are listed on the Indonesia Stock Exchange 2016-2020. The type of research is quantitative associative with secondary data types with data collection techniques in the form of documentation studies and literature studies. The results showed that partially the rupiah exchange rate had a significant effect of 14.65% on stock prices where the value of tcount > ttable (1.758 > 1.734), BI7DRR had no significant effect of 0.48% on stock prices t test, tcount < ttable (0.293 < 1.734), the JCI has a significant effect of 21.25% on stock prices and t-test, tcount > ttable (2.204 > 1.734), and simultaneously there is a significant effect between the rupiah exchange rate, BI7DRR, and the JCI of 44.68% on stock prices. PT Bank BJB TBK and f test results where fcount > ftable (4,308 < 3,20)